Investigation on Light-Emitting Diode Indoor Grow Light for Lettuce Plant Growth - Mohamad Zamri, Nur Adilah; Mohammad Radzi, Nur Hanis (Evolution in Electrical and Electronic Engineering, 2023)
Indoor planting is new urban farming in this era but the lighting source is important for plant growth healthy. Thus, artificial light from lamps is used to replace sunlight to assist plant growth. The disadvantage of outdoor planting is the weather condition is unpredictable causing limited or stunted plant growth. Other than that, the risk of plating outdoors is that pests attack may cause plant damage. The purpose of this research is to design a light-emitting diode (LED) grow light panel and develop a prototype of indoor planting using LED light growth and compare the condition of the lettuce salad if using LED grow light instead of sunlight as a lighting source. In this investigation, calculations on the electricity bills of automation grow light system and the energy consumption was also carried out. Meanwhile, the automatic LED grow lights were created by using real-time clock (RTC) modules for the lights feeding automatically to indoor farming from 6 am to 10 pm for a continuous 16 hours with an Arduino as a controller. From this investigation, data was collected every 10 days. The data shows that the value of 10 leaves and 14 cm in height for the red LED grow light while 7 leaves and 10 cm in height for the blue LED grow light on the 30th day. From the result, the indoor plant can grow efficiently because there is no risk of plant damage. In addition, low electricity bills were obtained which is RM1.06 /month for the LED light energy consumption. It can be concluded that the LED growth light can produce healthier plant products in terms of the leaf growth and plant height of lettuce hydroponic if compared to sunlight.